2014
DOI: 10.5539/gjhs.v7n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Study of Survival Rate After Cardiopulmonary Resuscitation (CPR) in Hospitals of Kermanshah in 2013

Abstract: Background:After CPR, the follow-up of survival rate and caused complications are the most important practices of the medical group. This study was performed aimed at determining the follow-up results after CPR in patients of university hospitals in Kermanshah in 2014.Methods:In this prospective study, 320 samples were examined. A purposive sampling method was used, and data was collected using a researcher-made information form with content and face validity and reliability of r= 0.79. Data was analyzed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
4
21
1
3
Order By: Relevance
“…One study showed that in critical ward, the rate of successful CPR was 3.3% (Jaberi, Changizian, & Mazlomzadeh, 2011;Karetzky, Zubair, & Parikh, 1995) and in other ward, this rate vary from 13% to 33% (Abella et al, 2005;Brindley et al, 2002;Taffet, Teasdale, & Luchi, 1988), also the successful CPR reported from 8% to 16% in some other studies (Karetzky et al, 1995). In Goodarzis study which was conducted in hospital, The ultimate success rate of resuscitation was 10.6%, and at six-month follow-up survey data on patients after discharge, the long-term success rate of the resuscitation was as 8.87% (Goodarzi et al, 2015). As the successful CPR depends on several factors and because of this study carried out in the pre-hospital environment, thus the rate of success can be different in comparison with previous studies that assessed the CPR outcomes in hospital with enough personnel and equipment.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…One study showed that in critical ward, the rate of successful CPR was 3.3% (Jaberi, Changizian, & Mazlomzadeh, 2011;Karetzky, Zubair, & Parikh, 1995) and in other ward, this rate vary from 13% to 33% (Abella et al, 2005;Brindley et al, 2002;Taffet, Teasdale, & Luchi, 1988), also the successful CPR reported from 8% to 16% in some other studies (Karetzky et al, 1995). In Goodarzis study which was conducted in hospital, The ultimate success rate of resuscitation was 10.6%, and at six-month follow-up survey data on patients after discharge, the long-term success rate of the resuscitation was as 8.87% (Goodarzi et al, 2015). As the successful CPR depends on several factors and because of this study carried out in the pre-hospital environment, thus the rate of success can be different in comparison with previous studies that assessed the CPR outcomes in hospital with enough personnel and equipment.…”
Section: Discussionmentioning
confidence: 94%
“…The successful CPR rate in other studies are as follow: 28.1% in Kermanshah (Saifi et al, 2010b), 29.3% in Shohadaye Haftom Tir, Tehran , 28.4% in selected educational centers of Tehran (Salari & Mohammadnejad, 2010), 19.9% in educational centers of Kashan (Ebell et al, 1998), 32% in Social Security emergency hospitals of Alborz Province (Nasiripour, Masoudi, & Fathi, 2012), 39.7% in Brazil (Moretti et al, 2007), 10.6% in Kermanshah (Goodarzi et al, 2015). One study showed that in critical ward, the rate of successful CPR was 3.3% (Jaberi, Changizian, & Mazlomzadeh, 2011;Karetzky, Zubair, & Parikh, 1995) and in other ward, this rate vary from 13% to 33% (Abella et al, 2005;Brindley et al, 2002;Taffet, Teasdale, & Luchi, 1988), also the successful CPR reported from 8% to 16% in some other studies (Karetzky et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that this may have a great effect on the final result. For example, Goodarzi et al (19) studied the survival rate of CPR for 6 months and found that the survival rate decreased from 15.3% to 8.78%. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%